Early Diagnosis of Dental Caries Using Fuzzy Inference The Sugeno Method System - Winda Antika Putri; Agung Triayudi; Ira Diana Solihati (Institute of Computer Science (IOCS), 2020)
Many are not aware of the dangers of oral health, especially dental caries. In 2018 the proportion of dental caries in Indonesia was 45.3%, according to the results of the Basic Health Research (RISKESDAS). Until now, dental health services have not reached the middle and lower class of society due to the very high cost. One way to make it easier for the public to recognize the disease's characteristics and diagnose dental caries as early as possible is to make an expert system application. The system in this application is made using the Sugeno fuzzy method. System testing yields an accuracy of 93%.